Multilingualism on screen: When liminality meets translation. The case of Jane The Virgin in French and Spanish translation - Bosseaux, Charlotte (Meta, 2023)
Multilingualism can be used to show how identity and characterisation are negotiated through language use. However, linguistic diversity is often homogenised in translation. In this paper, multilingualism is seen as a liminal space in products in which hyphenated identities are constructed through linguistic diversity. Translating multilingualism in this context is crucial since, if it is turned into monolingualism, this will limit the possibilities for new meanings to be introduced to new target cultures. I present a case study on the American television series Jane The Virgin (2014-2019) in which English and Spanish coexist, and the ability to understand and speak Spanish is an integral part of the characters’ identity and relationships. Comparing the French and Spanish versions points to homogenisation: the analysis ultimately demonstrates that since multilingualism can be understood as a liminal in-between space, its translation should be carefully considered so that new concepts of hyphenated identity and liminality can endure in translation.